Physicochemical and functional properties of cowpea protein isolates treated with temperature or high hydrostatic pressure - Peyrano, Felicitas (2016)
Fil: Peyrano, Felicitas. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.